Surveillance of Antimicrobial Resistance in Salmonella, Shigella, and Virvio cholerae in Latin America and the Caribbean: A Collaborative Project - David L Woodward; Frank G Rodgers (Canadian Journal of Infectious Diseases)
Diarrheal disease is recognized as the most frequent cause of morbidity and mortality in children worldwide (1). Current estimates indicate that at least 3.5 million children under the age of five years die each year due to diarrhea (1). Indeed, the World Health Organization (WHO) and the Pan American Health Organization (PAHO) have identified acute gastroenteritis as a major health problem in all Latin American countries (2). Mortality associated with acute diarrhea is highest among infants younger than one year of age, and death rates average 20/1000 children born (2). The impact of lives lost, together with the high costs to local public health care systems associated with treatment of those afflicted, make prevention and control of diarrheal disease a priority health issue (2). Over the past decade, these concerns have been further reinforced by the emergence of antimicrobial resistance among the major groups of enteric pathogens causing disease.